Shirley Jackson's "The Lottery" : the authorized graphic adaptation - Hyman, Miles (Hill and Wang a division of Farrar, Straus and Giroux, 2016)
A graphic novel adaptation of Shirley Jackson's "The Lottery" in which the people of a village perform their annual lottery, with startling consequences for the recipient of the one paper with the black spot.